2005
DOI: 10.1051/kmae:2005006
|View full text |Cite
|
Sign up to set email alerts
|

Macroparasite Community and Asymmetry of the Yellow Eel Anguilla Anguilla in Salses-Leucate Lagoon, Southern France

Abstract: European eel parasites, in particular invasive species, are suspected to have a strong influence on the population dynamics of their host. The aim of this work was to study the relationship between parasitic fauna of yellow eels caught at Salses-Leucate lagoon and the fluctuating asymmetry (FA) of some functional bilateral traits: pectoral fins, eyes and otoliths. Epidemiological distance matrices and FA distance matrices were calculated on the basis of the Euclidian distances between each pair of eel and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…was not found in Salses-Leucate lagoon, except in July 2004. A previous study showed that records of P. anguillae in Salses-Leucate lagoon were anecdotal (Fazio et al, 2005). This result suggests unfavourable environmental conditions for the parasite in this site.…”
Section: Salsesleucatementioning
confidence: 80%
“…was not found in Salses-Leucate lagoon, except in July 2004. A previous study showed that records of P. anguillae in Salses-Leucate lagoon were anecdotal (Fazio et al, 2005). This result suggests unfavourable environmental conditions for the parasite in this site.…”
Section: Salsesleucatementioning
confidence: 80%
“…Campbell and Emlen (1996) failed to find a significant relationship between FA of five meristic characters in chinook salmon O. tshawytscha and bacterial kidney infection caused by Renibacterium salmoninarum. Fazio et al (2005) likewise found no relationship between parasite load and FA for fin, eye, or otolith measurements in the eel Anguilla anguilla, nor did Loot et al (2001) find a relationship between Ligula intestinalis infestation and FA in a number of morphometric characters in roach Rutilus rutilus. Landrum (1966), Downhower et al (1990), Shaikin (1992), Bergstrom and Reimchen (2000, Lajus (2001), Lajus et al (2003), Prieto et al (2005) Natural stressors…”
Section: Fish Fluctuating Asymmetry Studiesmentioning
confidence: 94%
“…Rearing density Leary et al (1991Leary et al ( , 1992 Condition Jarvi et al (1996), Somarakis et al (1997b), Sanchez-Galan et al (1998), Folkvord et al (2000, Sunderland (2001), Robinson and Wardrop (2002), Bakker et al (2006), Gronkjaer and Sand (2003), Fey and Hare (2008) Infection/parasites Escos et al (1995), Campbell and Emlen (1996), Berg et al (1997), Reimchen (1997), Reimchen and Nosil (2001a, b), Loot et al (2001), Reimchen (2002, 2005), Fazio et al (2005), Prieto et al (2005), Pecinkova et al (2007) Predators/predation Moodie and Reimchen (1976), Moodie (1977), Bergstrom and Reimchen (2003) Anthropogenic stressors…”
Section: Abiotic Variablesmentioning
confidence: 99%
See 2 more Smart Citations